A Case of Bilateral Auricular Chondritis in a Heifer - Hibret A. Adissu; John D. Baird; Geoffrey A. Wood (Case Reports in Veterinary Medicine)
Auricular chondritis is an extremely rare condition in cattle and other domestic animals. A 13-month-old Jersey heifer was presented with cutaneous papillomatosis and bilaterally droopy ears. Histopathology revealed bilateral auricular chondritis characterized by lymphoplasmacytic infiltrate and extensive destruction and fibrosis of the auricular cartilage.